Effect of Eccentric Tension on the Response of Wrinkle Defects in Carbon Fiber-Reinforced Composite Laminates - Li Ma; Kaidi Ying; Ange Wen; Jing Guo; Jinyang Zheng (Energies, 2022)
Composite pressure vessels (CPVs) have become the main equipment for hydrogen storage; however, the effect of defect in the laminates of CPVs is difficult to detect. In this paper, composite specimens containing wrinkle defects were investigated, and a heterogeneity model of a wrinkle defect is proposed. A three-dimensional finite element code was developed to predict the behavior of carbon fiber-reinforced composite laminates with wrinkle defects. The effect of the geometric asymmetry of clamping was distinguished from the whole response. It was found that wrinkle defects are sensitive to tension but completely insensitive to torsion and that the distortion of out-of-plane displacement is strongly dependent upon wrinkle defects. An optical–mechanical method based on fringe projection was presented to measure the response of wrinkle defects, which shows an outstanding performance on wrinkle location and deformation visualization.